Implanted Intrathecal Drug Delivery Systems and Radiation Treatment. Issue 3 (21st February 2013) - Gebhardt, Rodolfo; Ludwig, Michelle; Kirsner, Steve; Kisling, Kelly; Kosturakis, Alyssa K.
Abstract Purpose. Radiotherapy affects the functioning of pacemakers. Guidelines based on dosimetric data exist regarding tolerable doses to pacemakers. Little is known about the effects of radiation on implantable drug delivery systems (IDDS). The objective of our study is to evaluate the safety of radiation treatment delivered to patients with IDDS. Methods and Materials. We evaluated patients who received external beam radiation therapy in our department after implantation of an IDDS between January 1, 2000 and November 30, 2011. Information was collected on IDDS function, treatment goals, treatment fields, prescribed doses, treatment energies, and cumulative radiation doses to the pump and the catheter. Results. A total of 39 patients received 60 separate courses of radiation therapy, of which 12 patients received radiation with either the pump or the catheter in the field. The remaining patients received scatter radiation only. The goal of radiation was palliative in all but one of the patients. Cumulative pump doses ranged from 5 to 36 Gy, and catheter doses ranged from 15 to 45 Gy. Beam energies ranged from 6 to 18 MV photons. All devices were checked after the completion of radiotherapy with a median follow‐up of 4.5 months, and all were found to be in good working condition. Conclusions. IDDS failures related to external beam radiation therapy seem to represent a rare occurrence. While we do not see reason to limit radiotherapy in patients with IDDS, we recommend device check after the completion of radiotherapy as well as if the patient has an increase in pain or analgesic requirement.